Cooling of a conductive panel by using an elastic-stepped channel under a magnetic field - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier Ltd, 2025)
Effective utilization of solar panels, battery modules, electronic systems, and their integrated systems require novel thermal management techniques and efficient cooling solutions. In the present study, a novel channel cooling system with a nano-enriched magnetic field is proposed for cooling a conductive panel. A numerical model for forced convection of flow over a forward-facing step with elastic bottom walls is considered along with the conduction in the panel under a uniform magnetic field by using Galerkin weighted residual finite element method (FEM). In numerical analysis, different values of flow Reynolds number (Re between 100 and 500), Hartmann number (Ha between 0 and 30), magnetic field inclination (? between 0 and 90), expansion ratio (ER between 0.75 and 4), and non-dimensional step location (XR between 0.2 and 0.75) are considered. Comparative studies are presented for separated flow features and cooling performance. At the highest Re, deformation of the elastic wall results in higher deflection of the wall. The average Nusselt number (Nu) rises by 86 percent and 89 percent for elastic and rigid wall cases when varying Re from minimum to maximum. The resulting temperature drop of the conductive panel becomes 11 °C and 11.3 °C. Higher magnetic field strength leads to higher cooling performance. At the highest magnetic field strength, average Nu rises by about 18 percent, while at the highest inclination, it is 15.3 percent at ER=4. The corresponding panel surface temperature drops become 5 °C and 3.9 °C. Higher values of ER and XR result in cooling performance deterioration. When a nano-enhanced magnetic field is used with a stepped channel, the temperature drops 23.5 °C at Re=100 and 32.6 °C at Re=500 when compared to the reference case (flat cooling channel without magnetic field and with water). The results and proposed cooling method can be utilized for further development and optimization studies related to the thermal management of solar panels, battery modules, and electronic cooling applications. © 2025
Keywords: Elastic wall; Finite element method; Hybrid nanofluid; Magnetic field; Stepped channel